Temperature-independent hygrometry using micromachined photonic crystal fiber - Zhang, Pan; Yang, Hangzhou; Lim, Kok Sing; Ahmad, Harith; Rong, Qiangzhou; Tian, Qin; Ding, Xiangzi (Optical Society of America, 2018)
An in-fiber Mach–Zehnder interferometer (MZI) is proposed and experimentally demonstrated for relative humidity (RH) and temperature measurements. The MZI is formed by a grapefruit-shaped photonic crystal fiber (G-PCF) cascaded with a short section of multimode fiber that serves as a mode coupler. To enhance sensitivity to humidity, femtosecond laser micromachining was performed to remove a portion of cladding of the G-PCF to expose its core to the ambient medium. The output interference spectrum is fast Fourier transformed to produce a spatial frequency spectrum that describes the intensity composition of the cladding modes in the MZI. In our investigation, it was observed that the interference dip intensity has a sensitivity of −0.077 dB=% RH to the change of RH in the range of 25%–80% RH, whereas the dip wavelength has a temperature sensitivity of ∼3.3 pm∕°C in the range of 25°C–70°C. In addition, the dip intensity was insensitive to temperature. These characteristics have provided convenience in eliminating temperature cross talk and achieving accurate humidity measurement.